Aplicação da matriz de avaliação na seleção de adições minerais utilizadas na composição de concretos para estacas pré-moldadas - Sousa, Matheus Claudino de (2021)
Foundations are extremely important for the execution of a building because they guarantee stability. The use of a foundation that is not adequate results in increased costs during execution, as well as during operation, and can cause problems in the structure of the building, whose correction can be costly or even unfeasible. Precast concrete piling is an excellent alternative for short construction deadlines, helps to obtain environmental seals, and reduces the amount of construction waste. The correct selection of raw materials and execution of the foundation is paramount to ensure the best performance of the building during its lifetime. The environmental and economic issue justifies the study, reducing the environmental impact by including materials in the composition of concrete and the cost of mineral additions are lower than cement. In this monograph, a rational selection method between two types of mineral admixtures, silica active and metacaulim, in the composition of concrete for precast cut piles It aims to select the mineral addition that ensures better performance of precast pile caps concrete among the parameters chosen for the analyses. Literature data was analyzed to find the maximum content of cement substitution for the mineral additions. From the pose of the required data and among the parameters compressive strength, tensile strength, and water absorption, the evaluation matrix selected the mineral addition that obtained the highest weight versus grade value.